Studying musical theatre : theory and practice - Taylor, Millie; Symonds, Dominic (New York : Palgrave Macmillan, 2014)
"The ideal accompaniment to any study of musical theatre, this lively textbook provides a comprehensive overview of the history, theory and practice of this popular theatre form. Bringing critical theory and musical theatre together, Millie Taylor and Dominic Symonds explore the musical stage from a broad range of theoretical perspectives, including narrative theory, orientalism, gender theory and globalization.Focusing on opera as well as musical theatre, Studying Musical Theatre considers dozens of diverse shows from 1607 to the present day. From Monteverdi to Mamma Mia, and from HMS Pinafore to Hedwig, this book offers an accessible and up-to-date guide to musical theatre for students, aficionados and enthusiasts alike"--
Machine generated contents note: -- List of Illustrations -- Acknowledgements -- Introduction -- PART I: READING TEXTS -- 1. 'A tale as old as time': Narrative Theory -- 2. 'A man who can interpret could go far': Semiotics and Semiology -- 3. 'Razzle dazzle 'em': Reception Theory and the Epic Musical -- 4. 'Life is a cabaret': Cultural Materialism -- PART II: INTERPRETING CONTEXTS -- 5. 'You've got to be carefully taught': Orientalism and Musical Theatre -- 6. 'I wanna be a producer': Globalization, Capitalism and Consumerism -- 7. 'What's the buzz?' Meta-narratives and Postlinearity -- PART III: PERFORMING IDENTITIES -- 8. 'Marry the man today': Feminism and the Performance of Identity -- 9. 'The bitch of living': Youth Cultures, Power, and Sexuality -- 10. 'I am what I am': Sexuality and Queer Theory -- PART IV: RETHINKING RELATIONSHIPS -- 11. 'It's the last midnight': Playing with Time and Space -- 12. 'I'm just a Broadway baby': Intertextuality in Music and Lyrics -- 13. 'Dreamgirls will make you happy': The Pleasures of Voice and Body -- 14. 'Make 'em laugh': The Politics of Entertainment -- Bibliography -- Index.
Keywords: Musicals -- History and criticism; Musical theater -- History; PERFORMING ARTS / Theater / General; PERFORMING ARTS / Theater / History & Criticism; PERFORMING ARTS / Theater / Broadway & Musical Revue